Perbandingan tahap kualiti hidup bagi warga emas yang mendapatkan perkhidmatan di Pusat Aktiviti Warga Emas (PAWE) di kawasan bandar dan luar bandar - Sarin Johani; Khadijah Alavi; Mohd Suhaimi Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2018)
The quality of life is an indicator of well-being that is seen as important in the establishment of policies to improve the welfare of senior citizens. The establishment of the Elderly Activity Center (PAWE) in urban and rural areas throughout Malaysia is one of the government's initiatives in preparation to be an old country by 2030. Nevertheless, since the establishment of PAWE in 2001, there has been scarce research about services provided to senior citizens at PAWE. Therefore, this study is conducted to identify level of quality of life among senior citizens at PAWE in urban and rural areas. The survey was conducted on 156 respondents in four PAWE locations namely PAWE Sungai Buloh, PAWE Cheras, PAWE Jenjarom and PAWE Sabak Bernam. The data were collected by using Older People Quality of Life (OPQOL-35) questionnaire. The data were then analyzed using Statistical Package Social Science (SPSS) by using descriptive analysis to identify the quality of life according to the respondents' demographic information. The results showed that the quality of life among urban respondents were higher than rural respondents, quality of life of male respondents were higher than female respondents while the quality of life among Chinese respondents was higher than Malay and Indian respondents. For the quality of life according to age, respondents aged 71 to 80 years were higher in qulity of life level than respondents aged 60 to 70 years and 81 to 90 years. This study is expected to give impact on the awareness to concerned parties about the advantages of community-based activity center which can increase the qualilty of life among elderly.